¬Writing and pictures on the Gravestones of the Cemetery of the Village of Kawrgosk: Analytic field study - Narmin Ali Muhamad Amin; Barzan Rasheed Mhamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Gravestones are of great importance in the study of archeology and are mean of accessing a lot of information due to the presence of writings and images on Gravestones. This is field research in the area of kawrgosk, the village of kawrgosk, which is part of the Khabat district in the Erbil governorate. To show a significant aspect of the civilizational aspects of this region, which were not previously covered by any scientific study. This study includes an analysis of the stone of the three tombs, although some of the broken stones were modified, but broken pieces were able to be reconnected, because of the period, environmental and human factor. It is the first field study that deals with these Gravestones from a technical and engineering point of view, as we focused on the field aspect as an essential part of the study, due to the lack of sources and references on the subject of research in particular and the region in general.